Making of Boksi and Bearing its Pain by Tamang Women of Kavrepalanchok - Zoowa, Sabin Bahadur (Nepal Journal of Sociology, 2024)
This study examines the sociological dimensions of witchcraft, prevalent in the Tamang community of Kavrepalanchok District, aiming to understand who the witches are in the village and why they are labeled as such. Within the supernatural belief system of the Tamang, witchcraft is deeply embedded in cultural practices and is often associated with internal family feuds, which can involve land disputes, inheritance issues, and complex community tensions. These conflicts frequently lead to the physical and psychological abuse of women in the community. The role of the Bombo, who sanctions and perpetuates these accusations, is central to understanding the social dynamics at play. Based on fourteen months of intermittant fieldwork, this study empirically demonstrates the social suffering that Tamang women endure when they are accused of being Boksi by their fellow Tamang members, whether family, community members, or faithhealers. The paper argues that the imagery of witchcraft is deeply entrenched in the Tamang community and that the concept of Boksi represents something that exists within individuals rather than externally. It adeptly illustrates the interplay between accuser and witchcraft, which is deeply rooted in family and societal conflict, envy, insecurity, and competition.